Studies on some free living protozoan from Salim Ali lake. Aurangabad - Shaikh, J D; Shaikh, T T; Kamble, U P; Jadhav, T J; Kazim, Malik (International Multidisciplinary Research Journal, 2012)
Protozoa are one-celled animals found worldwide in most habitats. Most species are free living, but all higher animals are infected with one or more species of protozoa. Infections range from asymptomatic to life threatening, depending on the species and strain of the parasite and the resistance of the host. Present study deals with the free living protozoa inhabiting fresh water bodies. The factor which influence their distribution and population in a given water bodies temperature, light, pH, chemical composition, acidity, and amount of food present in water and degree of adaptability of the individual protozoa to various environmental changes.